1996: the OECD policy-making assemblage. Issue 5 (3rd September 2022) - Thompson, Greg; Sellar, Sam; Buchanan, Ian
ABSTRACT: Recent analyses of education policy have used the concept of the assemblage to explain how the Organisation for Economic Cooperation and Development's education work contributes to global policy convergence and new forms of policy mobility. These analyses often use Deleuze and Guattari's concepts of assemblage to designate relations between things (as actors) and people (as actors). In this paper, we argue that Deleuze and Guattari's assemblage thinking offers promising analytical insights that education policy studies have not fully explored. We propose that revisiting the problematics which animated Deleuze and Guattari's assemblage theory can broaden the conceptual apparatus at our disposal for analysing global education policy and the work of international policy actors.